Peran Penyuluh Agama dalam Upaya Pemberantasan Buta Huruf Al-Qur’an di Kecamatan Gurah Kabupaten Kediri - Fatia Salma Fiddaroyni; Idatul Hurumi; Nurun Nikmatus Sobah; Ibnu Hajar Ansori (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2022)
Reading the Qur'an is one of the basic skills that every Muslim needs to have. Therefore, Qur'anic Education is among the earliest infrastructures that operate in every Islamic civilization, including in Indonesia. One of the important but unfortunately forgotten actors in Qur'anic Education is the Penyuluh Agama. Studies on Qur'anic Education have so far paid attention to the institutions of Qur'anic Education, both traditional ones such as pesantren, and modern ones, such as TPQ, Integrated Islamic schools, and so on, but neglect the role of Penyuluh Agama. Thus, this study is important to uncover one of the forgotten actors in the scholarship on Qur'anic Education. This study wants to address that gap. So, the question to be discussed in this article is how is the practice of Qur'anic education organized by Penyuluh Agama? This research takes the case of Qur'anic education organized by the Office of Religious Affairs (Kantor Urusan Agama, KUA) of Gurah District, Kediri Regency, East Java. Using field observations, interviews and documentation, this study describes the practice of Qur'ānic education that takes place in Gurahdistrict. The study shows that despite the existence of various Qur'ānic education institutions, both traditional and modern, Religious Extension Officers have a role in learning and teaching how to read the Qur'ān properly and correctly, through training organized at a time that suits the age group.